Acetabular Version Measurement in Total Hip Arthroplasty: The Impact of Inclination and the Value of Multi-Planar CT Reformation. Issue 1 (February 2015) - Loftus, Michael; Ma, Yan; Ghelman, Bernard
Background : The orientation of the acetabular cup component of a total hip arthroplasty can be evaluated in a number of ways, utilizing a myriad of imaging techniques and measurement parameters, including intraoperative surgical estimates, postoperative radiographs, and cross-sectional imaging such as computed tomography (CT) and magnetic resonance imaging (MRI). Questions/Purposes : How do traditional versus corrected measurements of acetabular version vary from one another based on the inclination of the cup? What is the reliability of the corrected acetabular version measurements based on interobserver and intraobserver consistency? Patients and Methods : Two fellowship-trained musculoskeletal radiologists reviewed CT scans on 60 total hip arthroplasties. Acetabular inclination, traditional CT acetabular version, and CT acetabular version corrected for inclination (by utilizing multi-planar reformations to measure in the plane of the cup face) were each measured. The difference was then calculated between the "traditional" axial CT and "corrected" acetabular version measurements, and the association between this difference and the acetabular inclination was assessed. Results : The "traditional" axial CT and "corrected" acetabular version measurements differed from one another in every case, with the traditional method yielding a version measurement that was on average 9.5° higher than the corrected technique. However, as the acetabular cup inclination angle decreased, the "traditional" measurement became more variable and increasingly discordant with the "corrected" version measurement. Conclusions : There is inherent variability between the many methods utilized for defining and measuring acetabular version, with axial CT measurements often used as an accepted proxy for true cup anteversion. However, the variability between different measurement techniques is correlated with acetabular inclination, and this variability is most pronounced when acetabular inclination is low, ultimately leading to potential confusion in measurement terminology. The increasingly widespread availability of multi-planar CT reformations provides an opportunity to standardize methodology, eliminate the impact of inclination on acetabular version measurements, and potentially provide a more reliable comparison of the impact of cup orientation on surgical outcomes.